The Legal Istinbath Method in The Mui Fatwa Mut’ah Marriage - Imel Lia; Syafik Muhammad; Apik Anitasari Intan Saputri (Journal Of Legal Studies Judex Praetor, 2025)
The Indonesian Ulema Council (MUI) fatwa on mut'ah marriage is implemented through the legal istinbath method, which in this method is the process of determining the law based on Islamic legal sources such as the Qur'an, Hadith, Ijma, and Qiyas. This study aims to determine the legal istinbath method of the Indonesian Ulema Council in formulating a fatwa on mut'ah marriage, as well as to determine what factors cause the Indonesian Ulema Council in formulating a fatwa on mut'ah marriage. In conclusion, the MUI fatwa and most scholars state that mut'ah marriage is haram, because this marriage is a marriage where a man marries a woman for a short time and for a certain time, while the purpose of marriage itself is to build a family that is sakinah mawadah wa rahmah. In this study the method used is the normative legal approach method where this research only uses literature studies or relies on books rather than field research.